The administrative and social impact of Nuri al-Said in Iraq (Journal of the College of Basic Education, 2025)
Abstract : The research deals with some of the works and effects of Nuri al-Said, the former Prime Minister of Iraq, in the administrative and social fields in Iraq, as it is not possible to talk about the history of contemporary Iraq without going through the role of Nuri al-Said, as he left clear fingerprints in various aspects of life in Iraq during the royal era, especially during his periods of working at the head of the executive authority as a minister and prime minister for fourteen times. Al-Said's personality was distinguished by important features and characteristics, which distinguished him from other administrators and politicians who held high positions in Iraqi governments throughout the royal era, especially his political acumen and quick wit in taking appropriate positions and decisions despite his opponents describing him as having a shallow culture and weak Arabic language, and his abilities in oratory and oratory, which enabled him to confront administrative and social problems and greetings, so he left clear fingerprints in those areas, taking advantage of his good relations with tribal leaders and sheikhs, as he was certain that without controlling the tribes, Iraq could not be ruled and stability achieved in it. In addition, his good social relations and the simplicity of his dealings with the middle classes of merchants, the poor, the businessmen, and the retirees, and even with his servants and guards, had an important impact on increasing his popularity in various classes of society, except for those who opposed him and his policy from political opponents. The great work he did in the field of lands, taxes, combating administrative and financial corruption, and following up on the needs of the market and its economic crises had a clear impact in addressing a large part of society’s problems, especially those of living and those that touch people’s daily lives .